The effect of motivation and the work environment on performance at the Juhar Camat Office Karo District - Sabar LT Simatupang (JURNAL GLOBAL MANAJEMEN, 2021)
This study aims to determine the effect of motivation and the work enviroment on employee performance at Kantor Camat Juhar Kabupaten Karo. The number of samples in this study were 18 respondents who were Civil Servants at the Office of the Sub-District Head of Mark Karo Regency. Library research and field research were used in this research. Data were analyzed using multiple linear regression analysis, and hypothesis testing was performed using ttest, Ftest and determination coefficient test. The results of the study obtained multiple regression equations Y=2,290-0,158X1+0,766X2, which explains that the regression coefficients possessed by the variables of ability and work experience give a positive direction to the performance of the employees of the Karo District Head Office. Based on hypothesis testing, it is found that motivation has a positive and significant effect on employee performance, with a tcount (-0,649)> ttable value (2,109).Work enviroment has a positive and significant effect on employee performance, with a tcount (5.038)> a ttable value (2,109. Motivation and work enviroment simultaneously have a positive and significant effect on employee performance, as indicated by the value of Fcount (38,875) > Ftable (3,59. The coefficient of determination test results also showed that 82,9% of employee performance variables could be explained by the variables of knowledge and work experience. While the remaining 17,1% is explained by other variables not examined in this study